Financial impact of regulatory sanctions on French listed companies - Laure de Batz (Charles University in Prague, Institute of Economic Studies (IES), 2018)
This paper assesses the information content of sanctions of listed companies pronounced by the French Financial Market Authority, through reactions from financial markets over the period 2004 to 2016. We answer whether, for a listed company, being named in a sanction report, as an offender, an acquitted, or a victim of others' financial misconduct conveys information to the market using an eventstudy methodology, complemented with cross-sectional regression analysis: do investors react to such news, and if so, at which stage of the procedure, to what extent, and why? We find that the markets do react accordingly to the information content of the sanctions. Guilty listed companies experience significant negative abnormal returns after both the sanction decision, and its publication (respectively -0.9% and -1.1% from the day preceding the event until 3 days after), though to a limited extent in absolute and relative terms. Some factors will contribute to stronger underperformances such as being investigated, longer procedures, being a smaller company possibly from financial or technological sectors, stronger media coverage of the sanctions, and better economic activity. The markets also incorporate the information content of the decision: no statistically significant abnormal reaction follows the publication of anonymized sanctions; market reactions vary depending on the regulatory breaches, being stronger for third party offenses; and, to some extent, the severity of the decision influences the magnitude of abnormal returns. Settlements do not convey information to the market, being a lighter and shorter procedure, associated with lower sanctions. Being sentenced non-guilty implies a mixed correction on the market, depending on the step of the procedure. Finally, companies named in a sanction report as victims of others' regulatory breaches also suffer negative abnormal returns after the sanction, suggesting double punishment.
Keywords: G14; G18; K42; N24; 330; Sanction; Financial Markets; Event Study; Regulation; Fraud; Information and Market Efficiency; Listed Companies